Community mental health nursing (CMHN) training on mental health cadres in Kulonprogo - Puji Sutarjo; Yayi Suryo Prabandari; Susi Iravati (Berita Kedokteran Masyarakat (BKM), 2016)
The effect of community mental health nursing training on the self efficacy and skills of the mental health cadresPurposeThis study aimed to know the effect of community mental health nursing training to self efficacy and skills of mental health cadres in early detection of severe mental illness symptoms in Banyuroto village, Nanggulan district, Kulon Progo. MethodsThis research was a quasi-experimental study using pre-post tests with control group. The treatment group were 32 health cadres who were given community mental health nursing training and the control group were 33 cadres who were not given community mental health nursing. ResultsBased on the pre-post tests, it was shown that there was a significant effect on the self efficacy and skills enhancement. ConclusionThere was an effect of community mental health nursing training using lectures, demonstrations, and role play methods on the self efficacy enhancement and skills of the mental health cadres in performing severe mental illness symptom early detection (psychosis).